(untitled) (Scientific journal of the Fergana State University, 2026)
The article studies the theoretical and methodological foundations of the development of socio-cultural competence in future teachers, the technological foundations of the development of socio-cultural competence in future teachers based on the subject of "Ethnoculture", the effectiveness of the development of socio-cultural competence in future teachers. The methodological content of the development of socio-cultural competence in future teachers based on the subject of "Ethnoculture" is also analyzed.